2021
DOI: 10.1073/pnas.2021671118
|View full text |Cite
|
Sign up to set email alerts
|

ZYP1 is required for obligate cross-over formation and cross-over interference inArabidopsis

Abstract: The synaptonemal complex is a tripartite proteinaceous ultrastructure that forms between homologous chromosomes during prophase I of meiosis in the majority of eukaryotes. It is characterized by the coordinated installation of transverse filament proteins between two lateral elements and is required for wild-type levels of crossing over and meiotic progression. We have generated null mutants of the duplicated Arabidopsis transverse filament genes zyp1a and zyp1b using a combination of T-DNA insertional mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
145
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(157 citation statements)
references
References 68 publications
12
145
0
Order By: Relevance
“…For instance, in barley it was reported that dramatic reduction of normal levels of ZYP1 by RNAi also drastically reduce CO formation (Barakate et al, 2014). However, in the case of Arabidopsis and rice a malfunctioning SC does not affect recombination and may even increase CO frequency and abolish CO interference (Wang et al, 2010;Capilla-Perez et al, 2021;France et al, 2021). In both holocentric Rhynchospora and Luzula it was shown that they apparently have conserved SC structures as immunostaining with SC proteins showed the conserved pattern for monocentric species (Cabral et al, 2014;Heckmann et al, 2014).…”
Section: Meiotic Recombination In Holocentric Plantsmentioning
confidence: 99%
“…For instance, in barley it was reported that dramatic reduction of normal levels of ZYP1 by RNAi also drastically reduce CO formation (Barakate et al, 2014). However, in the case of Arabidopsis and rice a malfunctioning SC does not affect recombination and may even increase CO frequency and abolish CO interference (Wang et al, 2010;Capilla-Perez et al, 2021;France et al, 2021). In both holocentric Rhynchospora and Luzula it was shown that they apparently have conserved SC structures as immunostaining with SC proteins showed the conserved pattern for monocentric species (Cabral et al, 2014;Heckmann et al, 2014).…”
Section: Meiotic Recombination In Holocentric Plantsmentioning
confidence: 99%
“…COs are formed in the context of the meiotic axes and the synaptonemal complex (SC) and physically link homologous chromosomes to enable correct segregation. The SC is a protein structure that builds on the axes, tightly connects homologous chromosomes and is required for inter-homolog recombination and interference ( Zickler and Kleckner, 1999 ; Kleckner, 2006 ; Mercier et al, 2015 ; Smith and Nambiar, 2020 ; Capilla-Perez et al, 2021 ; France et al, 2021 ). The repair of the residual breaks yields NCO products, possibly via synthesis-dependent strand-annealing, intersister recombination, or non-homologous end-joining ( Higgins et al, 2004 ; Chen et al, 2008 ; Mancera et al, 2008 ; Sims et al, 2019 ).…”
Section: Meiosismentioning
confidence: 99%
“…Meiocytes of plants lacking axis proteins, such as ASY1 and ASY3, never fully synapse ( Caryl et al, 2000 ; Ferdous et al, 2012 ) and full pachytene stages are also not observed in cohesion-deficient mutants like scc3 and rec8 ( Bai et al, 1999 ; Chelysheva et al, 2005 ). Similarly, complete synapsis is not observed when the transverse filament ZYP1 proteins are depleted or absent ( Higgins et al, 2005 ; Osman et al, 2006 ; Capilla-Perez et al, 2021 ; France et al, 2021 ). During wild-type pachytene (and up to diakinesis), ZMM proteins MSH4/5 and HEI10, as well as MLH1/3, localize to CO sites and form around 9–11 bright foci per nucleus, corresponding to the average number of chiasmata.…”
Section: Meiotic Stages (Observed Under the Widefield Microscope)mentioning
confidence: 99%
See 1 more Smart Citation
“…ASYNAPTIC 1 (ASY1) is a chromosome axis-associated protein, which plays a major role in the initiation of synapsis and recombination (Armstrong et al, 2002; Caryl et al, 2000; Sanchez-Moran et al, 2007). ZIPPER 1 (ZYP1) encodes for a component of the transversal element of the synaptomenal complex (SC), which is thought to be crucial for the maturation of COs and CO interference (Capilla-Perez et al, 2021; France et al, 2021; Higgins et al, 2005; Osman et al, 2006).…”
Section: Resultsmentioning
confidence: 99%